Hadist Tematik: Manajemen Dalam Kepemimpinan Pendidikan Islam - Radia Hijrawan (SALIHA: Jurnal Pendidikan & Agama Islam, 2021)
Management is a product that is needed by an organization or instasi, management is a way of working that is implemented or implemented. A superior organization or agency will apply its work system, of course all of this is carried out by the head of the agency or organization. Every effort, activity and deliberate action to achieve a goal must have a good and strong foundation as well as the legality of its implementation. Therefore, especially for educational institutions, an effort to shape human beings must have a solid foundation and legality of implementation and plan goals to be achieved. In this study using the literature study method (Lebrary Raserach), from the results of the study that a leader in an organization must have management knowledge to manage human resources, as the Prophet Muhammad SAW has exemplified, using management functions both in planning, organizing, mobilization and surveillance, an event of war to prepare his troops, he also arranged the strategy or position of his soldiers, the goal was to gain victory even though they were less numerous than the enemy